DETERMINAN STRUKTUR MODAL SEKTOR PROPERTIES & REAL ESTATE DI BEI PERIODE 2013 – 2023 - AULIA YAGHFIRA; SATRIYO WIBOWO (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
The purpose of this research is to examine and analyze the impact of profitability, growth opportunities, firm size, liquidity and tangibility on capital structure. The study focuses on companies in the Properties & Real Estate sector listed on Indonesia Stock Exchange during the 2013-2023 period. The research sample consists of 26 companies, totaling 286 data, selected using a purposive sampling method. Data analysis was conducted using multiple linear regression. The results indicate that profitability, growth opportunities, and liquidity influence capital structure. However, firm size and tangibility do not have effect on capital structure.